PENGARUH MODEL PAP TERHADAP HASIL BELAJAR PKN DI SEKOLAH DASAR NEGERI - Ika Sapalega; Marzuki Marzuki; Tahmid Sabri (Universitas Tanjungpura, 2019)
AbstractThis research aimed to describe the contribution of the model picture and picture technique toward students’s learning outcomes civics education in elementary school south pontianak. This research used Experiment method with (Pre-experimental design). The population of thi reearch are all tudent of Grade IV that included 20 people. Baed on data analyt obtained data analysis an average grade 60,19 pre-test and post-test average of 71,05. The results of hypothesis testing using t-test obtained t = 6,57 and α = 0.05% is obtained t table of 1.729, which means that (thitung> ttabel) so Ha is received. Thus, it can be concluded that the model picture and picture technique provides high impact on learning outcomes Civics Class IV Keywords : Cooperative Learning, Model Picture and Picture, Result Study.